PENGEMBANGAN RUMPUT GAJAH SEBAGAI PAKAN SAPI DI OPHIR NAGARI KOTO BARU KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Yayuk Sri Utami (Jurnal Hilirisasi IPTEKS, 2020)
The Opir area is located in Nagari Koto Baru, Luhak Nan Duo District, West Pasaman Regency. This area has a large area of land that has great potential in developing beef cattle. Increasing the beef cattle population really requires the availability of quality and sustainable feed. Elephant grass is one type of forage / superior grass with a high nutritional content used as cow feed. The development of elephant grass is to provide good quality forage. Elephant grass has a lot of biomass production, can be harvested several times a year; even this forage is easy to cultivate. The purpose of the activity is to provide education and proper and correct elephant grass cultivation techniques, land optimization, and improve the quality of forage as beef feed. This training activity was held in Jorong Ophir, Nagari Koto Baru, West Pasaman Regency. The activity methods used are socialization, counseling, demonstration, and evaluation. The targets of this activity are farmers and communities in Ophir, Nagari Koto Baru. The results of the activity showed that the participants as the target of the activity were very enthusiastic and gave good responses. Extension of elephant grass cultivation started from land preparation, planting, maintenance and harvesting. In this activity, farmers increase their knowledge and skills in determining good elephant grass seeds and proper and correct elephant grass cultivation techniques. It is hoped that this activity can be carried out sustainably by breeders to optimize land and availability of good quality and sustainable forage as animal feed to increase livestock productivity.